Extracting secret keys from integrated circuits. - Daihyun Lim (IEEE Transactions on VLSI systems)
Modern cryptographic protocols are based on the premise that only authorized participants can obtain secret keys and access to information systems. However, various kinds of tampering methods have been devised to extract secret keys from conditional access systems such as smartcards and ATMs. Arbiter-based physical unclonable functions (PUFs) exploit the statistical delay variation of wires and transistors across integrated circuits (ICs) in manufacturing processes to build unclonable secret keys. We fabricated arbiter-based PUFs in custom silicon and investigated the identification capability, reliability, and security of this scheme. Experimental results and theoretical studies show that a sufficient amount of inter-chip variation exists to enable each IC to be identified securely and reliably over a practical range of environmental variations such as temperature and power supply voltage. We show that arbiter-based PUFs are realizable and well suited to build, for example, key-cards that need to be resistant to physical attacks.